Postoperative Acute Exacerbation of IPF after Lung Resection for Primary Lung Cancer - Watanabe, Atsushi; Kawaharada, Nobuyoshi; Higami, Tetsuya (Pulmonary Medicine, 2011)
Idiopathic pulmonary fibrosis (IPF) is characterized by slowly progressive respiratory dysfunction. Nevertheless, some IPF patients experience acute exacerbations generally characterized by suddenly worsening and fatal respiratory failure with new lung opacities and pathological lesions of diffuse alveolar damage. Acute exacerbation of idiopathic pulmonary fibrosis (AEIPF) is a fatal disorder defined by rapid deterioration of IPF. The condition sometimes occurs in patients who underwent lung resection for primary lung cancer in the acute and subacute postoperative phases. The exact etiology and pathogenesis remain unknown, but the condition is characterized by diffuse alveolar damage superimposed on a background of IPF that probably occurs as a result of a massive lung injury due to some unknown factors. This systematic review shows that the outcome, however, is poor, with postoperative mortality ranging from 33.3% to 100%. In this paper, the etiology, risk factors, pathogenesis, therapy, prognosis, and predictors of postoperative AEIPF are described.